Pengaruh Islamic Marketing dan Corporate Image terhadap Customer Satisfaction dan Customer Loyalty Luwak White Koffie - Sabda Ramadhan (Jurnal Wacana Ekonomi, 2019)
This research was motivated by problems related to Islamic Marketing and Corporate Image of Luwak White Koffie especially in the city of Garut. Based on the overall pre survey results on consumers of Luwak White Koffie, it is known that consumers have not shown maximum satisfaction and have not shown loyalty to Luwak White Koffie products and even show a tendency to shift to competitor products, which is based on the author's opinion due to intense competition in Indonesian coffee industry. This study aims to determine the effect of Islamic Marketing and Corporate Image on Customer Loyalty through Customer Satisfaction of Luwak White Koffie, especially those who lived in the city of Garut. This study uses a quantitative method with a type of descriptive and causal research. Sampling method in this research uses non probability sampling specifically purposive sampling, with number of respondents as many as 100 peoples, while the data analysis technique uses descriptive analysis techniques and path analysis. Descriptive analysis result shows that the Islamic Marketing, Corporate Image, Customer Satisfaction are in the good category, while the Customer Loyalty is in a fairly good category. Result of the calculation of path analysis shows that Islamic Marketing and Corporate Image variables jointly influences Customer Loyalty through Customer Satisfaction Luwak White Koffie.